Paleopathology and Nutritional Analysis of a South German Monastery Population. (6th August 2015) - Nerlich, Andreas G.; Riepertinger, Alfred; Gillich, Ralph; Panzer, Stephanie
Abstract : The monastery of Attel, Upper Bavaria, which was founded in AD 1030, harbours a series of crypt burials from the time period between AD 1700 and 1750. Due to a restoration of the church, 16 crypts had to be removed and were subjected to an extensive anthropological-paleopathological and isotope analysis. The 16 crypts contained 19 burials in open wooden coffins. All bodies were covered by an extensive layer of calcium carbonate. Despite this "treatment, " bone and teeth were excellently preserved (mean degree of conservation > 75%, completeness > 85%). The anthropological investigation revealed a mean age of 38.5 years and a body height of 1.71 m. Paleopathologically, a surprisingly high rate of trauma was seen (13 injuries in 7 different individuals, i.e., 36.8% of individuals affected), 2 cases presented signs of extensive arthritis urica (gout), and several monks were affected by arthrosis of shoulder and knee joints. Extensive dental attrition, numerous foci of dental caries, and dentogenic abscesses coincided with considerable dental calculus indicating poor oral hygienic conditions. Stable isotope analysis showed adequate mixed carnivore-herbivore nutrition, comparable to that of contemporaneous upper class individuals. This extensive combined analysis provides considerable insight into the nutrition and disease pattern of a middle-class monastery of early 18th century South Germany.